Analisis Potensi Relief Sri Tanjung Candi Surawana Sebagai Materi Media Pembelajaran Komik Sejarah - Afandi, Alifia Nurhusna (Jurnal Pendidikan Sejarah Indonesia, 2025)
On Surawana Temple, several beautiful reliefs are engraved, one of which is the relief of Sri Tanjung. The story of Sri Tanjung itself contains life values that can be used as a lesson. However, not much has been done to introduce the story of Sri Tanjung, especially to students through learning media. So that the writing of this article aims to find out the reliefs of Sri Tanjung at Surawana Temple, the story of Sri Tanjung in history lessons, and the potential of the Sri Tanjung Reliefs at Surawana Temple as learning media material for historical comics. The research method used is descriptive qualitative method. Research techniques using observation and documentation. The results of the study show that the relief of Sri Tanjung in Surawana Temple has the meaning of ruwatan, consisting of several panels that tell the story of the dispute between Sidapaksa and Sri Tanjung until they reunited. The story of Sri Tanjung has character values such as hard work, honesty, responsibility, and religion which can be included in history lessons. The integration process can be done through learning methods, selecting or making teaching materials and learning media. The relief of Sri Tanjung at Surawana Temple has the potential to be used as a historical comic because the pictures are arranged sequentially and form a story like a storyline in a comic. Making comics can provide benefits such as making it easier for students to grasp material, and taking a positive side that will support student character development.